2016
DOI: 10.4184/asj.2016.10.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor Analysis for C5 Palsy after Double-Door Laminoplasty for Cervical Spondylotic Myelopathy

Abstract: Study DesignA retrospective comparative study.PurposeTo clarify the risk factors related to the development of postoperative C5 palsy through radiological studies after cervical double-door laminoplasty (DDL).Overview of LiteratureAlthough postoperative C5 palsy is generally considered to be the result of damage to the nerve root or segmental spinal cord, the associated pathology remains controversial.MethodsA consecutive case series of 47 patients with cervical spondylotic myelopathy treated by DDL at our ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
0
24
1
Order By: Relevance
“…At the time of acute recirculation, the nerve cells may be chemically damaged by reactive oxygen 92,93) . In contrast, in the theory of nerve root injury, the anterior rootlet or nerve root may be mechanically compressed and/or distracted 58, [94][95][96][97][98][99][100][101] .…”
Section: B Postoperative C5 Palsymentioning
confidence: 99%
“…At the time of acute recirculation, the nerve cells may be chemically damaged by reactive oxygen 92,93) . In contrast, in the theory of nerve root injury, the anterior rootlet or nerve root may be mechanically compressed and/or distracted 58, [94][95][96][97][98][99][100][101] .…”
Section: B Postoperative C5 Palsymentioning
confidence: 99%
“…Concerning the kinds of nerve tissue involved, there are two theories: 1) the segmental spinal cord disorder theory 18,19) and 2) the nerve root injury theory 9,[20][21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Conjectured Causes Of C5 Palsymentioning
confidence: 99%
“…By contrast, in nerve root injury theory, C5 palsy is thought to be caused by mechanical compression and/or the distraction of the anterior rootlet and/or anterior nerve root 9,[20][21][22][23][24][25][26][27][28][29][30][31] . From this theory, the features of C5 palsy can be well explained.…”
Section: Conjectured Causes Of C5 Palsymentioning
confidence: 99%
See 1 more Smart Citation
“…C5 palsy can result from a posterior shift of the spinal cord (PSSC) after laminoplasty 4,6,7) . Baba et al reported a significantly larger PSSC at C4/5 in patients with postoperative C5 palsy compared to those without palsy (odds ratio, 12.066; P = 0.029; 95% confidence interval, 1.295-112.378), indicating that the tethering phenomenon is a likely risk factor for postoperative C5 palsy 8) . On the other hand, Uematsu et al reported a significantly higher incidence of radiculopathy after cervical laminoplasty when the bony gutter was cut on the lateral side of the medial aspect of the zygapophyseal joint 9) .…”
Section: Introductionmentioning
confidence: 99%